2013
DOI: 10.1038/ncomms2823
|View full text |Cite
|
Sign up to set email alerts
|

GANP regulates recruitment of AID to immunoglobulin variable regions by modulating transcription and nucleosome occupancy

Abstract: Somatic hypermutation in B cells is initiated by activation-induced cytidine deaminase-catalyzed C→U deamination at immunoglobulin variable regions. Here we investigate the role of the germinal centre-associated nuclear protein (GANP) in enhancing the access of activation-induced cytidine deaminase (AID) to immunoglobulin variable regions. We show that the nuclear export factor GANP is involved in chromatin modification at rearranged immunoglobulin variable loci, and its activity requires a histone acetyltrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 52 publications
3
50
0
Order By: Relevance
“…Further, strong nucleosome positioning sequences have been shown to impair diversification (Kodgire et al , 2012). We therefore asked whether the reduced R‐loop formation in h3.3 cells reflected a change in the distribution of nucleosomes across the locus by mapping the average nucleosome positions in IGVL in wild‐type and h3.3 cells using micrococcal nuclease treatment coupled to quantitative PCR (Singh et al , 2013). This revealed two centres of nucleosome occupancy in IGVL of wild‐type cells (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Further, strong nucleosome positioning sequences have been shown to impair diversification (Kodgire et al , 2012). We therefore asked whether the reduced R‐loop formation in h3.3 cells reflected a change in the distribution of nucleosomes across the locus by mapping the average nucleosome positions in IGVL in wild‐type and h3.3 cells using micrococcal nuclease treatment coupled to quantitative PCR (Singh et al , 2013). This revealed two centres of nucleosome occupancy in IGVL of wild‐type cells (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…DNA regions with DSBs initiated by intensive targeting of AID must be repaired during the interphase before the mitotic phase of the cell cycle to rescue and generate IgV region diversity in daughter Ag-reactive B cells. Our proteomics analysis revealed that GANP is associated with DNA-PKcs prominently among the DNA repair molecules (34). Given that GANP interacts with DNA-PKcs, it might be the initial member of the DNA repair pathway interacting with the AID/GANP complex in situ at the IgV region loci in germinal center B cells.…”
mentioning
confidence: 88%
“…Samples were prepared with anti-H4 and anti-acetyl H4 Abs (Cell Signaling Technology), as previously described (33,34), and examined using Mesa Blue qPCR MasterMix Plus (Eurogentec) on the Applied Biosystems ViiA 7 with reported primers (37).…”
Section: Ganpmentioning
confidence: 99%
See 1 more Smart Citation
“…B2 cells are selected as naive B cells of the non-self-reactive primary repertoire in the bone marrow, which are distributed to peripheral lymphoid organs. Ag stimulation with the help of Th cells induces rapid expansion of naive B cells in the germinal centers (GCs) of lymphoid follicles, where Ag-reactive B cells undergo somatic hypermutation (SHM) of IgV region genes and class switch recombination (CSR) at the S regions by AID (24)(25)(26)(27)(28)(29). Thus, B2 cells gain IgV region SHM and CSR in the GCs of lymphoid follicles to become high-affinity Ag-reactive and IgG Ab-producing plasma cells (30).…”
mentioning
confidence: 99%